Approaches to Decrease Hyperglycemia by Targeting Impaired Hepatic Glucose Homeostasis Using Medicinal Plants - Mata-Torres, Gerardo; Andrade-Cetto, Adolfo; Espinoza-Hernández, Fernanda (Frontiers in Pharmacology, 2021)
Liver plays a pivotal role in maintaining blood glucose levels through complex processes which involve the disposal, storage, and endogenous production of this carbohydrate. Insulin is the hormone responsible for regulating hepatic glucose production and glucose storage as glycogen, thus abnormalities in its function lead to hyperglycemia in obese or diabetic patients because of higher production rates and lower capacity to store glucose. In this context, two different but complementary therapeutic approaches can be highlighted to avoid the hyperglycemia generated by the hepatic insulin resistance: 1) enhancing insulin function by inhibiting the protein tyrosine phosphatase 1B, one of the main enzymes that disrupt the insulin signal, and 2) direct regulation of key enzymes involved in hepatic glucose production and glycogen synthesis/breakdown. It is recognized that medicinal plants are a valuable source of molecules with special properties and a wide range of scaffolds that can improve hepatic glucose metabolism. Some molecules, especially phenolic compounds and terpenoids, exhibit a powerful inhibitory capacity on protein tyrosine phosphatase 1B and decrease the expression or activity of the key enzymes involved in the gluconeogenic pathway, such as phosphoenolpyruvate carboxykinase or glucose 6-phosphatase. This review shed light on the progress made in the past seven years in medicinal plants capable of improving hepatic glucose homeostasis through the two proposed approaches. We suggest that Coreopsis tinctoria, Lithocarpus polystachyus, and Panax ginseng can be good candidates for developing herbal medicines or phytomedicines which target inhibition of hepatic glucose output as they can modulate the activity of PTP-1B, the expression of gluconeogenic enzymes, and the glycogen content.